2020
DOI: 10.1167/jov.20.7.29
|View full text |Cite
|
Sign up to set email alerts
|

Implicit responses to face trustworthiness measured with fast periodic visual stimulation

Abstract: People rapidly and spontaneously form trustworthiness impressions based on facial appearance. Studies using functional magnetic resonance imaging find that activity in the amygdala and other brain regions tracks with face trustworthiness, even when participants are not explicitly asked to judge face trustworthiness. The current study investigated whether it would be possible to detect implicit responses using another method: fast periodic visual stimulation (FPVS). While scalp electroencephalogram (EEG) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 52 publications
4
11
0
Order By: Relevance
“…This result suggests that facial trustworthiness can be processed implicitly, without needing instructions to judge trustworthiness. Using a similar FPVS oddball face individuation paradigm, Verosky et al (2020) also found evidence of implicit trustworthiness processing. Together these results suggest that the FPVS oddball response can be used as an objective and reliable neural marker of trustworthiness processing.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…This result suggests that facial trustworthiness can be processed implicitly, without needing instructions to judge trustworthiness. Using a similar FPVS oddball face individuation paradigm, Verosky et al (2020) also found evidence of implicit trustworthiness processing. Together these results suggest that the FPVS oddball response can be used as an objective and reliable neural marker of trustworthiness processing.…”
Section: Introductionmentioning
confidence: 84%
“…All participants first completed the implicit size condition so that our comparison of task instructions benefitted from a within-participant design. In this initial block, we also aimed to replicate the recent finding that an FPVS signal can be found in response to faces changing in trustworthiness in the absence of explicit trust judgement instructions ( Swe et al, 2020 ; Verosky et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, trait information can be extracted from faces quickly (Willis & Todorov, 2006), spontaneously (Klapper et al, 2016), unconsciously (Freeman et al, 2014; Getov et al, 2015) and attractiveness impressions, at least, may be mandatory (Ritchie et al, 2017). Recent electrophysiological studies using the fast periodic visual stimulation technique have also established that a neural signal can be found in response to changes in trustworthiness in rapidly presented face images, without requiring instructions to judge trustworthiness (Swe et al, 2020; Verosky et al, 2020). It has yet to be established whether face‐based impressions are automatic in the sense of being capacity‐free.…”
Section: Introductionmentioning
confidence: 99%